2023
DOI: 10.3390/su15043695
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of the Spatiotemporal Characteristics of the Eco-Environmental Quality in the Chishui River Basin from 2000 to 2020

Abstract: The Chishui River Basin is located in the bordering area of Yunnan, Guizhou and Sichuan provinces, which serves as an important ecological barrier in the upper reaches of the Yangtze River, and plays a leading role in preserving natural environments, protecting water resources, and maintaining soil functions. However, the eco-environmental quality in the basin has encountered serious challenges in recent years, and the conflict between eco-environmental protection and economic development becomes increasingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Furthermore, population density has consistently been the most significant influencing factor in previous studies. For example, in the same studies as those mentioned above, population density was the first influencing factor for EEQ in the Chishui Basin [33] and the second influencing factor for EEQ in the Taihu Basin [24]. In addition, studies on the EEQ in the Three Gorges Ecological Corridor region have noted that population density is always one of the top three influencing factors in different years [21].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, population density has consistently been the most significant influencing factor in previous studies. For example, in the same studies as those mentioned above, population density was the first influencing factor for EEQ in the Chishui Basin [33] and the second influencing factor for EEQ in the Taihu Basin [24]. In addition, studies on the EEQ in the Three Gorges Ecological Corridor region have noted that population density is always one of the top three influencing factors in different years [21].…”
Section: Discussionmentioning
confidence: 78%
“…However, in previous studies, the explanatory power of the elevation factor on EEQ was relatively weak. For example, in the Taihu Lake region [24], elevation ranked fourth in terms of explanatory power among seven factors; in the Chishui River region [33], elevation also ranked fourth. Furthermore, population density has consistently been the most significant influencing factor in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to integrating four easily accessible ecological evaluation indicators, namely green, dry, wet and heat, the RSEI also uses a Principal Component Analysis (PCA) to automatically and objectively weight each indicator. There have been numerous studies using this method to quantify and accurately evaluate EQ [9], such as those conducted in watersheds [10][11][12], mining areas [13,14], wetlands [15,16], cities [17][18][19][20], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of remote sensing technology has provided substantial data for ecosystem monitoring [5] . Different scholars discussed the land use change and ecological environment quality in different regions based on remote sensing ecological index, and found that human activities had a great impact on ecological environment [6][7][8] . To explore the comprehensive impact of water resources development and utilization on the ecological environment, definition of the ecological environment quality scientifically, and formulation of the corresponding scientific countermeasures are conducive to the ecological system gradually entering a virtuous circle and the regional development towards a sustainable direction.…”
Section: Introductionmentioning
confidence: 99%